Cadmium as the Critical Limiting Factor in the Co-Disposal of Municipal Solid Waste Incineration Fly Ash in Cement Kilns: Implications for Three-Stage Water Washing Efficiency and Safe Dosage Control - Zhonggen Li; Qingfeng Wang; Li Tang; Liangliang Yang; Guangyi Sun (Toxics)
The co-disposal of municipal solid waste incineration fly ash (MSWI-FA) in cement kilns is an effective method for managing incineration by-products in China. However, the presence of heavy metals in MSWI-FA raises environmental concerns. This study analyzed the Cu, Zn, Cd, Pb, Cr, and Ni concentrations in MSWI-FA from 11 representative facilities across China and assessed the efficacy of a three-stage water washing process for Cl and heavy metal removal. The results revealed significant regional variations in heavy metal content that were strongly correlated with surface soil levels, with Zn, Pb, and Cu exhibiting the highest concentrations. Elemental correlations, such as Cu-Pb and Zn-Cd synergies and Cd-Ni antagonism, suggest common waste sources and temperature-dependent volatilization during incineration. The washing process (solid–liquid ratio = 1:10) achieved 97.1 ± 2.0% Cl removal, reducing residual Cl to 0.45 ± 0.32%, but demonstrated limited heavy metal elimination (10.28–19.38% efficiency), resulting in elevated concentrations (32.5–60.8% increase) due to 43.4 ± 9.2% mass loss. Notably, the washing effluents exceeded municipal wastewater discharge limits by up to 52-fold for Pb and 38-fold for Cd, underscoring the need for advanced effluent treatment. To mitigate environmental risks, the addition of washed MSWI-FA in cement kilns should be restricted to ≤0.5%, with Cd content prioritized in pre-disposal assessments. This study provides actionable insights for optimizing MSWI-FA co-processing while ensuring compliance with ecological safety standards.